Magnitude, causes and management of avoidable blindness: A cross-sectional study in Pravara Rural Hospital of Rural Medical College, Maharashtra, India - Avachat, Shubhada; Kamble, Suchit; Phalke, Deepak; Bangal, Surekha; Zambare, Mrinal (South East Asia Journal of Public Health, 2013)
There are an estimated 180 million people worldwide who have a visual impairment. Out of that number, nearly 45 million are blind and four out of five of them live in developing countries. One-third of the world's blind people (15 million) and 50% of the world's blind children (0.7 million) live in the South-East Asia Region. Approximately 90% of all the cases of blindness in this region are avoidable. The present study was conducted in a tertiary health center, Pravara Rural Hospital of Rural Medical College Loni, Maharashtra, India, to examine the magnitude of preventable causes of blindness and to investigate the various causes responsible for blindness along with treatment offered. Out of 703 patients examined in the ophthalmology department in January 2011, 588 (83.6%) patients had avoidable blindness 525 from the outpatient department and 63 from the inpatient department. The Most common cause was cataract (60.95%), followed by refractive error (26%), whereas vitamin A deficiency and retinopathy were least common causes of avoidable blindness in our study. The baseline data presented by the present study about magnitude, causes and management of avoidable blindness will help to make 'Vision 2020' successful. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13225 South East Asia Journal of Public Health 2011:1:68-70